Chromate Anion Adsorption on Iron Hydroxide - S. Mustafa; A. Jamal; A. Naeem; N. Rehana (Adsorption Science & Technology)
Chromate anion adsorption on iron hydroxide was studied as a function of pH (3–9) and temperature (20–40°C). The adsorption of chromate anion was found to decrease with increasing pH and increase with increasing temperature. The data were explained with the help of the Kurbatov and modified Langmuir equations. The small effect of temperature indicated that chromate anion adsorption on iron hydroxide occurred through a mechanism involving outer - surface sphere complexation.